Combining chemical and genetic approaches to increase drought resistance in plants. Issue 1 (December 2017) - Cao, Min-Jie; Zhang, Yu-Lu; Liu, Xue; Huang, Huan; Zhou, X.; Wang, Wen-Long; Zeng, Ai; Zhao, Chun-Zhao; Si, Tong; Du, Jiamu; Wu, Wen-Wu; Wang, Fu-Xing; et al.
Abstract Drought stress is a major threat to crop production, but effective methods to mitigate the adverse effects of drought are not available. Here, we report that adding fluorine atoms in the benzyl ring of the abscisic acid (ABA) receptor agonist AM1 optimizes its binding to ABA receptors by increasing the number of hydrogen bonds between the compound and the surrounding amino acid residues in the receptor ligand-binding pocket. The new chemicals, known as AMFs, have long-lasting effects in promoting stomatal closure and inducing the expression of stress-responsive genes. Application of AMFs or transgenic overexpression of the receptor PYL2 inArabidopsis and soybean plants confers increased drought resistance. The greatest increase in drought resistance is achieved when AMFs are applied to the PYL2-overexpression transgenic plants. Our results demonstrate that the combining of potent chemicals with transgenic overexpression of an ABA receptor is very effective in helping plants combat drought stress. Plants respond to abiotic stress via the phytohormone ABA. Here, Cao et al. report a series of new ABA receptor agonists, named AMFs, which have higher receptor-binding affinities and show that, when employed in tandem with ABA receptor overexpression, can significantly increase drought resistance